2013
DOI: 10.5539/ijbm.v8n21p14
|View full text |Cite
|
Sign up to set email alerts
|

Project Management Practices and Critical Success Factors–A Developing Country Perspective

Abstract: The study sought to identify and assess the quality of project management practices as well as the critical success factors for projects in Ghana. The study adopted an exploratory approach and utilized a survey method to collect data on project management practices of Ghanaian organizations. Purposive sampling was used in selecting the sample which comprised 200 managers from different economic sectors. Results from the study indicated that the critical factors that contribute to the success of a project inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 21 publications
3
68
0
6
Order By: Relevance
“…Purposive sampling was used in selecting the sample which comprised 200 managers from different economic sectors. Findings from the study revealed that the critical factors that contribute to the success of a project include top management support, effective communication, clarity of project purpose and goals, and stakeholder involvement Ofori(2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Purposive sampling was used in selecting the sample which comprised 200 managers from different economic sectors. Findings from the study revealed that the critical factors that contribute to the success of a project include top management support, effective communication, clarity of project purpose and goals, and stakeholder involvement Ofori(2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Project communication management, one of the areas of project management, is considered to be of crucial importance to the success of the project (Ofori, 2013;Kerzner, 2013), in particular IT projects (Holzmann, Panizel, 2013) carried out by dispersed teams (Tone et al, 2009;Sidawi, 2012;Niinimäki et al, 2012;Han, Jung, 2014). But even though its importance is generally acknowledged and communication practices are found to be associated with most of the project success dimensions, the communication processes formalized in the company's project management methodology are often ignored or not given enough attention (see, among others, Monteiro de Carvalho, 2013;Papke-Shields et al, 2010).…”
Section: Project Communication Management Characteristicsmentioning
confidence: 99%
“…Purna Sudhakar, 2012;Ofori 2013), in particular IT projects carried out by dispersed teams (Han, Jung, 2014;Niinimäki, Piri, Lassenius, Paasivaara, 2012). Effective project communications ensure that the right information reaches the right person at the right time and in a cost-effective manner, and it is a critical element of team effectiveness, both in traditional and virtual teams.…”
Section: Theoretical Backgroundmentioning
confidence: 99%